Vliv technologie provádění svislých konstrukcí na cenu objektu - Dvořák, Luboš (Vysoké učení technické v Brně. Fakulta stavební, 2012)
V teoretické části bakalářské práce byly uvedeny jednotlivé typy cen a způsoby oceňování, včetně mezinárodních oceňovacích standardů. V další teoretické části je uvedena historie v oblasti stavebnictví a typy konstrukcí a jejich provádění. V praktické části je zkoumáno 6 druhů svislých konstrukcí, které jsou porovnávány dle ceny, šířky zdiva a součinitele prostupu tepla. U jednotlivých konstrukcí je popsán způsob výstavby a jsou u nich zmíněny výhody a nevýhody. Výsledky jednotlivých konstrukcí jsou znázorněny v grafech a v závěru této práce je zmíněn jeden stavební materiál, který se jeví dle těchto kritérií, jako nejlepší.

The first theoretical part of the thesis quotes different types of prices and methods of pricing, including the international pricing standards. The second theoretical part deals with history of civil engineering, sorts of building structure and their construction. The practical part of the thesis examines 6 variants of vertical building structures considering their prices, thickness of walling masonry and overall coefficient of heat transfer. Every structures cover description of their construction inclusive making reference to pros and cons. The outcome of each structure is presented in graphs. At the end of the thesis, one particular building material is chosen as the best, in accordance with the criterion hereinbefore.
The Impact of the Implementation of the Wall Construction on the Building Construction Cost
Keywords: Nemovitost; svislá konstrukce; standard; cena; průzkum; vliv ceny; Immovable; vertical structure; standard; price; research; influence price